The Superwoman and Other Writings by Miriam Michelson - Michelson, Miriam, 1870-1942 (Book collections on Project MUSE., 2019)
Collection of articles and fiction by pioneering journalist and turn-of-the-twentieth-century feminist, Miriam Michelson.